An explorative study to inland waterway transport - the Rhine market - Olaf Jonkeren (European Regional Science Association (ERSA), 2005)
Since 1998 every form of regulation in the inland shipping market has been ruled out. As a result of years of setting minimum prices and dividing cargo's a situation of over-capacity has occurred. The situation of over-capacity still exists but now in a free market. This situation has some interesting implications.
Keywords: 330